A novel cystatin derived from Trichinella spiralis suppresses macrophage-mediated inflammatory responses. - Porntida Kobpornchai; Robin J Flynn; Onrapak Reamtong; Nonglucksanawan Rittisoonthorn; Nathamon Kosoltanapiwat; Kobporn Boonnak; Usa Boonyuen; Sumate Ampawong; Montakan Jiratanh; Muncharee Tattiyapong; Poom Adisakwattana (Public Library of Science (PLoS), 2020)
Trichinella spiralis can modulate host immune responses to retain a suitable environment for its long-term survival. Incidentally, the parasite elicits regulatory effects through immunomodulatory molecule release, which can suppress host inflammation and may be used for the treatment of unrelated inflammatory diseases in someday. Here we identified and characterized a novel T. spiralis cystatin (TsCstN), which inhibits inflammation mediated by LPS-treated macrophages.Proteins contained in the excretory-secretory (ES) product of muscle-stage T. spiralis (ES-L1) were fractionated, and each was treated with mouse bone marrow-derived macrophages (mBMDMs) before LPS stimulation. The fractions that exhibited high immunomodulatory property by decreasing pro-inflammatory cytokines or increasing anti-inflammatory cytokines were identified by mass spectrometry. Incidentally, the conserved hypothetical protein (Tsp_04814) was selected for further characterization as it presented the most significant MS score. An annotation of Tsp_04814 using protein structural homology comparison suggested that it has high structural similarity to human cystatin E/M (TM score 0.690). The recombinant T. spiralis novel cystatin (rTsCstN) was expressed in Escherichia coli at a molecular weight of approximately 13 kDa. Mouse anti-rTsCstN polyclonal antibody (pAb) could detect native TsCstN in crude worm antigens (CWA) and ES-L1 and be predominantly localized in the stichosome and subcuticular cells. rTsCstN inhibited cysteine proteases in vitro, especially cathepsin L, at an optimal pH of 6. Besides, rTsCstN could be internalized into mBMDMs, which were mostly distributed in the cytoplasm and lysosome both before and after LPS stimulation. To evaluate the rTsCstN immunomodulatory properties on mBMDMs, rTsCstN was incubated with mBMDM before LPS stimulation; this demonstrated that rTsCstN suppressed pro-inflammatory cytokine production and MHC class II expression.T. spiralis L1-derived TsCstN was characterized as a novel cysteine protease inhibitor. The protein elicits an anti-inflammatory property by suppressing pro-inflammatory cytokines and interfering with the antigen presentation process through depletion of MHC class II expression.